2017
DOI: 10.21276/apalm.2017.972
|View full text |Cite
|
Sign up to set email alerts
|

Bone Tumors and Tumor-like lesions: A study in a Tertiary Care Hospital, Mumbai

Abstract: Background: Bone tumors are one of the intimidate challenge to the orthopedic surgeon. This call out for even more concern in resource poor settings, in economically developing nations. We analysed bone tumours and tumour like lesions, their demographic features like age and sex distributions, anatomical sites of occurrence and their relative frequencies,clinico-pathological characteristics and histo-morphological features as seen in a tertiary care hospital of India.Methods: This is a retrospective study of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…These findings correlated well with the previous studies done by Bamnikar SA et al, Jain K et al, Baena Ocampo LC et al [12][13][14]. Pain and swelling (9 cases, 30.00%) was the most common overall clinical presentation as similar to Kumavat et al and Kokode [11,15]. In this further 50% of benign bone, tumors had pain and swelling while 21.43% of malignant tumors had pain and swelling.…”
Section: Figure 2: Sex Incidence In a Particular Category Of Bone Lesionssupporting
confidence: 91%
See 1 more Smart Citation
“…These findings correlated well with the previous studies done by Bamnikar SA et al, Jain K et al, Baena Ocampo LC et al [12][13][14]. Pain and swelling (9 cases, 30.00%) was the most common overall clinical presentation as similar to Kumavat et al and Kokode [11,15]. In this further 50% of benign bone, tumors had pain and swelling while 21.43% of malignant tumors had pain and swelling.…”
Section: Figure 2: Sex Incidence In a Particular Category Of Bone Lesionssupporting
confidence: 91%
“…The present study found an equal incidence of malignant bone tumors & benign bone tumors which is variable with the study done by Mohammad and Isa [10]. A commonest benign tumor in the current study was osteochondroma which is comparable with the study conducted by Kumavat et al and Bamanikar et al followed by multiple myeloma which is in concordance with the study by Jain et al [11][12][13]. The lesions ranged from 8-64 years with a mean age of 33.17 years.…”
Section: Figure 2: Sex Incidence In a Particular Category Of Bone Lesionssupporting
confidence: 90%
“…According to Kumavat et al [13] out of 216 cases of bone tumors Out of 216 cases, primary bone tumors were 151 (69.91%), metastatic tumors were 40 cases (18.52%) and tumor like conditions were 25 cases (11.58%). According to Sunita A.Bamanikar et.…”
Section: Discussionmentioning
confidence: 99%
“…4 Beside these all the histopathology provides accuracy in diagnosing these bone tumors or tumor like lesions. 5 Bone lesions may create diagnostic challenges to orthopaedic surgeons and surgical pathologists 6 , as the normal is composed of four types of elements including osteoid, cartilage, fibrous tissue and bone marrow, among which any element may be responsible for various benign and malignant neoplastic lesions. 7 Due to large variety of bone disorders, the exact diagnosis is very difficult clinically, and only exception to melanoma, the biochemical analysis is not much significant.…”
Section: Introductionmentioning
confidence: 99%